Analysis of Liquidity, Solvency, and Profitability Ratios to Assess Financial Performance at PT. Garuda Indonesia (Persero), Tbk - Yohana Chelsea T. Hebber; M. Irsan Nasution; Handriyani Dwilita (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the financial performance of PT Garuda Indonesia (Persero) Tbk for the 2019–2024 period using liquidity, solvency, and profitability ratios. The research method used is descriptive quantitative with secondary data in the form of annual financial reports. The results show that Garuda Indonesia's financial performance during this period is classified as unhealthy. Liquidity ratios (Current Ratio and Quick Ratio) are consistently below industry standards, indicating the company's inability to meet short-term obligations. Solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio) are also in the poor category, indicating the company's high dependence on debt funding and an unbalanced capital structure. Meanwhile, profitability ratios (Net Profit Margin, Return on Investment, and Return on Equity) have fluctuated significantly, with averages far below industry standards, except in 2022, which showed a brief recovery. It is concluded that PT Garuda Indonesia is experiencing serious financial pressure. Therefore, it is recommended that the company implement operational efficiency, debt restructuring, and asset optimization to improve liquidity, solvency, and profitability.